Penggunaan Dua Varietas Benih Bawang Merah Dan Takaran Pupuk Kandang Ayam Petelur Terhadap Pertumbuhan Dan Hasil Tanaman Bawang Merah - Julyadi; Yusnaweti Amir; Teguh Haria Aditia Putra (JURNAL AGROTEKNOLOGI UNIVERSITAS ANDALAS, 2025)
This study is about the use of two varieties of shallot seeds and the dosage of laying hen manure on the growth and yield of shallot plants. This study aims to obtain the best dosage of laying hen manure, the effect of interaction, the best varieties for shallot plants for the growth and yield of shallots. This research was conducted in the Experimental Garden of the Faculty of Agriculture, Muhammadiyah University of West Sumatra, Payakumbuh, with a research altitude of ± 514 m above sea level, from August to October 2024. The design used was a factorial Randomized Block Design (RAK) consisting of 2 factors, the first factor is the shallot variety consisting of two varieties, namely the Solok Sakato variety and the Bima Berebes variety. The second factor is 4 levels of laying hen manure treatment, namely (without treatment, 10 tons/ha, 20 tons/ha and 30 tons/ha. Data were analyzed statistically using the F test at a significance level of 5%, if the calculated F is greater than the F table, then continued with Duncan's New Multiple Range Test (DNMRT) at a significance level of 5%. The results of this study indicate that there is no significant interaction between the Solok Sakato shallot variety and the Bima Berebes variety with the provision of laying hen manure on growth and yield. The Solok Sakato variety produces the largest number of bulbs compared to the Bima Brebes variety. The provision of chicken manure with a dose of 20 tons per hectare can increase the growth and productivity of shallot plants optimally. The Solok Sakato variety reaches a production level of 6,028 tons/ha, while the Bima Brebes variety produces 5,615 tons/ha.